Kompetensi Dan Amalan Guru Cemerlang Bahasa Melayu Tentang Pengajaran Dan Pembelajaran Komsas - Subri, Mohd Rohiman (2022)
This study was conducted to examine competency and the practices of teaching and learning on literature component (komsas) among Malay Language Excellent Teachers. Seven informants were selected using purposive sampling technique and they were voluntarily participated in this research as research participant. Qualitative design based on phenomenological approach was employed in this study. The research objectives are focusing on (i) identifying the competencies of Malay language Excellent Teachers on the teaching and learning of komsas; and (ii) exploring the Malay Language Excellent Teachers practices in teaching and learning of komsas. In-depth interview data collection techniques were conducted in this study and data were analyzed using Nvivo 12 software with qualitative thematic analysis method. The findings of the study found that Malay Language Excellent Teachers’ competencies consist of knowledge that includes content knowledge, general pedagogical knowledge and pedagogical knowledge.